2018
DOI: 10.1097/qai.0000000000001563
|View full text |Cite
|
Sign up to set email alerts
|

HIV Continuum of Care for Youth in the United States

Abstract: Youth living with HIV in the United States can be successfully treated at health care sites with experience, excellence, and important resources and services. Sustained VL suppression may be an important step to add to the Continuum of Care for youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 17 publications
0
34
1
Order By: Relevance
“…One study of 525 children with perinatal HIV aged <18 years across the Netherlands in 2016 reported very high success rates with 96% on treatment, of whom 97% were virally suppressed ≤ 100 copies/mL . A study of 467 youth with horizontally acquired HIV aged 13 to 24 years in care across the USA during 2015 (of whom half had been diagnosed for less than 3 years) found 86% were engaged in care, of whom 98% were on ART, and of these 89% were suppressed <200 copies/mL . The proportion engaged in care in the USA study is substantially lower than in our cohort, this is possibly due to the difference in mode of infection and shorter duration since HIV diagnosis.…”
Section: Discussioncontrasting
confidence: 69%
“…One study of 525 children with perinatal HIV aged <18 years across the Netherlands in 2016 reported very high success rates with 96% on treatment, of whom 97% were virally suppressed ≤ 100 copies/mL . A study of 467 youth with horizontally acquired HIV aged 13 to 24 years in care across the USA during 2015 (of whom half had been diagnosed for less than 3 years) found 86% were engaged in care, of whom 98% were on ART, and of these 89% were suppressed <200 copies/mL . The proportion engaged in care in the USA study is substantially lower than in our cohort, this is possibly due to the difference in mode of infection and shorter duration since HIV diagnosis.…”
Section: Discussioncontrasting
confidence: 69%
“…The details of the study have been published elsewhere 17. Adolescents were approached at one of their scheduled clinic visits by trained clinic research staff.…”
Section: Methodsmentioning
confidence: 99%
“…From 1 of the largest national samples of adolescents and young adults living with HIV, distinct patterns of risk behaviors were identified, pointing to the importance of tailoring clinical and preventive interventions. A more recent longitudinal cohort study at 14 ATN sites across the United States also reported demographic and psychosocial characteristics of 467 youth living with HIV and assessed how the later steps of the HIV continuum of care were achieved over a 1-year period [14]. Among 32 studies with completed analyses, the ATN has published over 214 manuscripts and presented over 156 abstracts at various domestic and international scientific conferences.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have documented the challenges that youth experience maintaining adherence to their antiretroviral regimens, including side effects, medication dosing schedules, unstable living situations, disclosure of HIV status, co-occurring illnesses, and lack of health insurance [11-13]. Recent data, however, suggest that youth can be successfully treated at health care sites that have expertise in treating youth [14], whereby 59% of youth achieved sustained viral load suppression over the course of a year. Health care delivery and other interventions tailored to the unique needs of youth and their effects on HIV continuum of care outcomes need to be investigated further [15].…”
Section: Introductionmentioning
confidence: 99%